Improving Teacher Competence at SD Negeri 002 Lubuk Baja, Batam City, Through Principal Leadership - Wisnu Febri Susanto (CV. TOTUS TUUS, 2026)
This Community Service Program (PKM) aimed to improve teacher competence at SD Negeri 002 Lubuk Baja, Batam City, through strengthened principal leadership. The program responded to limited communication, delayed information, and insufficient professional guidance for teachers. It was conducted from September to October 2025 using a participatory and andragogical approach involving training, mentoring, simulation, group discussion, and evaluation. The activity emphasized transformational, democratic, participative, and instructional leadership to improve pedagogical, professional, social, and personality competence. The results showed that teachers' average competence score increased by 17.6%, from 73.2 in the pre-test to 86.1 in the post-test, with the highest improvement in professional competence (22.5%). The program also strengthened communication, collaboration, supervision, and teacher motivation.